Pengaruh Etos Kerja Terhadap Kinerja Pegawai Dengan Disiplin Kerja Sebagai Variabel Mediasi Pada Badan Kepegawaian Daerah Provinsi Jambi - Christiani Br Pintubatu; Rohman Wilian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to describe and determine the influence of work ethic on employee performance with work discipline as a mediating variable at the Jambi Province Regional Civil Service Agency. The analytical method used is quantitative analysis. The research population and sample were all employees at the Jambi Province Regional Civil Service Agency, totaling 81 respondents. Data collection was carried out by distributing questionnaires using a Likert scale. The statistical analysis used is the Structural Equation Modeling (SEM) technique with Partial Least Square (PLS) as an analysis tool, using the SmartPLS 4 program. The results of the statistical analysis show that work ethic has a positive and significant effect on employee performance, work ethic has a positive and significant effect on work discipline, work discipline has a positive and significant effect on employee performance, and work discipline is able to mediate the influence between work ethic and employee performance. So it can be concluded that work discipline functions as a link between work ethic and employee performance. Employees who have a good work ethic will work with discipline following company regulations so that their performance will increase and have a positive impact. This helps the company achieve its targeted goals.